Partisipasi Perempuan Dalam Pemilihan Calon Legislatif (Studi Deskriptif Di Desa Setanggor Kecamatan Sukamulia Kabupaten Lombok Timur) - Lalu Muhammad Abib Muammar; Muh. Mabrur Haslan; Samsul Hadi (Universitas Mataram, 2025)
This study aims to examine the level of women’s political participation in legislative elections, identify barriers, and analyze efforts to enhance participation in Setanggor Village, Sukamulia District, East Lombok Regency. Using a qualitative approach with ethnographic methods, data was collected through purposive sampling, involving election organizers, village officials, community leaders, and female voters. Semi-structured interviews, passive participation observation, and documentation were used for data collection. Miles and Huberman’s analysis model was applied, including data reduction, display, and conclusion drawing. The results show that women’s political participation is limited to formal involvement, such as voting, without substantial political awareness. Internal barriers include low education, political literacy, low self-confidence, and domestic workload, while external barriers involve patriarchy, religious influence, limited access to information, and weak institutional support. However, community-based political education, strengthening women’s organizations, and inclusive policies can enhance participation.